Understanding English Language Teachers’ Cognition About Students’ Use of AI: A Case Study at FPBU USIM - Saiful Izwan Zainal; Rahimah Saimin; Hazlina Abdullah; Noor Saazai Mat Saad; Engku Muhammad Syafiq Engku Safruddin (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia